At whose service? : Caribbean state posture, merchant capital and the export services option - Marshall, Don D. (2002)
Examines the current preference in the Eastern Caribbean for export services or international business as a strategy to militate against the harsh effects of globalization. Focuses on Barbados because it is mooted as a replicable model for others in the region to emulate.